A multilevel analysis of factors associated with vitamin A supplementation among children aged 6-35 months in Ethiopia - Tsegaw Amare; Tseganesh Sime; Gebrehiwot Lema Legese; Menberesibhat Getie Ferede; Melaku Birhanu Alemu (Frontiers Media S.A., 2023)
BackgroundVitamin A deficiency is among the leading preventable causes of childhood morbidity and mortality that might be attributable to the low uptake of vitamin A supplementation (VAS). Factors contributing to its low utilization are not researched at the national level and with the appropriate model. Therefore, this study aimed at identifying the magnitude and the individual- and community-level factors associated with vitamin A supplementation among children aged 6-35 months in Ethiopia.MethodsWe have used the Ethiopian mini demographic and health survey data, which was conducted from 21 March to 28 June 2019. A weighted sum of 2,362 mothers having children aged 6-35 was extracted. Considering the hierarchical nature of the data, we fitted the multilevel multivariable logistic regression model. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was reported and variables with a p-value of < 0.05 were declared to be significantly associated factors.ResultsIn this study, 43.4% (95% CI: 41.4-45.4%) of children have taken the VAS. Moreover, the 12-23 age of the child (AOR = 2.64; 95% CI: 1.88-3.72), 30-34 age of the mother (AOR = 3.34; 95% CI: 1.21-9.20), middle household wealth status (AOR = 1.75; 95% CI: 1.06-2.90), and four and above antenatal care (AOR = 2.90; 95% CI: 1.90-4.43) are the individual-level factors associated with VAS whereas being from Amhara (AOR = 2.20; 95% CI: 1.29-3.76) and Tigray (AOR = 2.16; 95% CI: 1.17-3.98) regions is a community-level factor significantly associated with the uptake of VAS.ConclusionOverall, a low proportion of children have taken the VAS in Ethiopia. The higher age of the child and mother, full antenatal care, and improved wealth status positively influence VAS. Moreover, a child from the Tigray or Amhara regions was more likely to get VAS. Therefore, an intervention has to be designed to address the VAS uptake among young mothers, and working to improve the wealth status of the household would be helpful. Moreover, the advocacy of antenatal care and minimizing the regional disparity through encouraging the uptake in the rest of the regions would help increase the national-level uptake of VAS.